PECULIARITIES OF THE USE OF COMPUTER TECHNOLOGIES IN TEACHING ENGINEERING GRAPHICS - Z. Ruzimurodova; D.K. Mamatov (Scholar Express Journal, 2021)
The main purpose of teaching computer graphics in school in the article is to teach students the order and rules of computer-aided drawing of graphic information, such as drawings, diagrams and schemes, performed in the disciplines of drawing and engineering graphics. The main task of "Computer Graphics" is to provide students with the knowledge and skills necessary for the free performance on the computer of design and creation of models of technological processes using practical and operational programs and ready-made packages
Keywords: Computer graphics; teaching; student; drawing; engineering graphics; science